GlassHands: Interaction Around Unmodiï¬ed Mobile Devices Using Sunglasses - Ofek, Eyal; Pahud, Michel; Grubert, Jens; Schmalstieg, Dieter; Kranz, Matthias (ISS 2016, 2016)
We present a novel approach for extending the input space around unmodiﬁed mobile devices. Using built-in front facing cameras of unmodiﬁed handheld devices, GlassHands estimates hand poses and gestures through reﬂections in sunglasses, ski goggles or visors. Thereby, GlassHands creates an enlarged input space, rivaling input reach on large touch displays. We introduce the idea along with its technical concept and implementation. We demonstrate the feasibility and potential of our proposed approach in several application scenarios, such as map browsing or drawing using a set of interaction techniques previously possible only with modiﬁed mobile devices or on large touch displays. Our research is backed up with a user study.